Protocol for semisynthesis of histone H4 with site-specific modifications using irreversible sortase-mediated ligation - Yihang Xiao; Kun Zou; Mingxuan Wu (STAR Protocols)
Summary: Post-translational modifications (PTMs) of histone H4 play significant roles in the regulation of chromatin status. Here, we present a protocol for semisynthesis of histone H4 by sortase-mediated ligation (SML). We describe steps for solid-phase peptide synthesis of H4R40C(1–42), recombinant expression and purification of H4(41–102), expression and purification of eSrt(2A-9), and preparation of acrylamidine. We then detail procedures for SML of histone H4. This protocol can also be applied to the preparation of homogenous proteins with PTMs.For complete details on the use and execution of this protocol, please refer to Xiao et al.1,2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.